Response to letter to the editor: Comparison of soft tissue and bone surgeries in the treatment of developmental dysplasia of the hip in 18-24-month-old patients - Bulut, Mehmet; Karakurt, Lokman (Lippincott Williams & Wilkins, 2014)
[Abstract Not Available]